Effects of Valopro Win Feeding Duration in Different Nursery Diet Types on Nursery Pig Growth Performance and Fecal Dry Matter - Julian Arroyave; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 300 pigs (DNA, Line 241 × 600; initially 12.3 ± 1.04 lb), were used to evaluate the effects of Valopro Win (VLPW) feeding duration on pig performance and fecal dry matter. Valopro Win contains a purified source of coarse indigestible fiber, oat hulls, and yeast autolysate. At weaning, pigs were blocked by body weight (BW) and then randomly assigned to pens and allotted to one of six dietary treatments in a 2 × 3 factorial arrangement, with main effects of formulation strategy (low ABC-4 without ZnO or high ABC-4 with ZnO) and VLPW feeding duration (0, 10, or 24 d). There were five pigs per pen and 10 pens per treatment. Experimental diets were formulated in two dietary phases from d 0 to 10 and d 10 to 24, with a common post-treatment diet fed from d 24 to 42. Low ABC-4 diets were formulated to 200 and 250 meq/kg from d 0 to 10 and d 10 to 24, respectively. High ABC-4 diets were formulated to 493 and 470 meq/kg and contained 2,990 and 1,910 ppm of Zn from ZnO from d 0 to 10 and d 10 to 24, respectively. Diets containing VLPW were formulated by replacing 2.5% of the diet with VLPW without making any nutritional adjustments. No interactions were observed (P > 0.10) between VLPW feeding duration and formulation strategy on any response criteria. There was no significant effect (P > 0.10) of VLPW feeding duration on growth performance; however, on d 10, pigs fed VLPW diets had increased fecal dry matter (P = 0.019). During the experimental period (d 0 to 24), pigs fed low ABC-4 diets with no ZnO had decreased (P < 0.001) ADG, d 24 BW, and lower ADFI compared with pigs fed high ABC-4 with ZnO, but no significant differences (P > 0.10) were observed in the overall period (d 0 to 42). On d 24, pigs fed low ABC-4 without ZnO diets had greater (P < 0.001) fecal dry matter than those fed high ABC-4 with ZnO. In conclusion, even though pigs fed high ABC-4 diets containing ZnO had improved growth during the experimental feeding period, neither the use of VLPW nor the formulation strategies significantly affected overall nursery performance. However, fecal dry matter was increased on d 10 when pigs were fed VLPW and at d 24 when pigs were fed low ABC-4 diets without ZnO.
Keywords: acid binding capacity; fecal dry matter; fiber; growth performance; nursery pig